The Role of Women in Iraq in Enhancing Climate Change Mitigation: A Vision and Analysis (Entrepreneurship Journal for Finance and Business, 2024)
Women role in achieving sustainable development becomes as a one of most important issues in societies in general and in Iraq as a special case. She has a great role as her partner (man) has especially in achieving economic development; instead of this fact but the path is still not clear and long to say that! Due to the global numbers that shared internationally without serious scientific logic treatment; where statistical numbers refer that Iraq still in level (154 out of 156) around the world; and for economic & educational sectors in specific, unfortunately Iraqi women register around (0.228/1) and (0.8/1) respectively as Global Economic Institute announced in 2021. In order to understand this fact, there is a benefit to review the real role of Iraqi women in establishing societies’ infrastructure and trying to decrease the gap especially in her role in education, health-care, in addition to employ and invest her innovative ideas into pioneer projects.